CT findings of small cell lung carcinoma: Can recognizable features be found?. Issue 47 (November 2016) - Lee, Dongjun; Rho, Ji Young; Kang, Seunghun; Yoo, Koun Joy; Choi, Hye Jeong
Abstract : Abstract: The purpose of this study was to clarify the recognizable computed tomography (CT) features of small cell lung carcinoma (SCLC). Contrast enhanced CT scans were reviewed retrospectively for mass location, mediastinal extension, and other concomitant findings in 142 patients with pathologically proven SCLC. SCLC was classified into hilar mass only (type I), hilar mass with ipsilateral mediastinal extension (type II), hilar mass with bilateral mediastinal extension (type III), and peripheral mass (type IV). When mediastinal lymphadenopathy (m-LAP) was indistinguishable from a hilar mass, we defined it as a mediastinal conglomerate mass (m-CM). Type IIa or IIIa had ipsilateral or bilateral m-LAP and type IIb, IIIb or IIIc had ipsilateral or bilateral m-CM. Type I (n = 8, 5.6%), type II (n = 58, 40.8%), type III (n = 55, 38.8%), and type IV (n = 21, 14.8%) were manifested. The combination of a hilar mass and m-CM was found in 68 patients (47.9%). Type IV masses showed lobulation in 11, microlobulation in 4, both lobulated and irregular margins in 4, and spiculation in 2. A total of 120 patients (84.5%) had a bronchial stenosis/obstruction; single (n = 52) and 2 or more (n = 68). Ninety-five patients (67.0%) had vascular invasion including main/lobar pulmonary artery and superior vena cava, and 55 (38.7%) had pleural effusion and/or pleural nodules. Concomitant parenchymal findings (n = 92, 64.8%) were noted: contiguous consolidation/nodule (n = 45), hematogeneous spread (n = 32), lymphangitic spread (n = 21), obstructive pneumonia (n = 22), and obstructive atelectasis (n = 14). In conclusion, the recognizable CT features of SCLC were a hilar mass with m-CM. Most of the hilar masses showed 2 or more bronchial stenoses/obstructions. Most cases of peripheral SCLC manifested as a lobulated mass rather than a spiculated mass. Vascular invasion and concomitant parenchymal findings were observed commonly.